2021
DOI: 10.1111/grow.12560
|View full text |Cite
|
Sign up to set email alerts
|

Rural e‐commerce in China: Spatial dynamics of Taobao Villages development in Zhejiang Province

Abstract: The fast-growing e-commerce has dramatically changed the economic structure of China's rural area. As a unique example, Taobao Villages present a brand-new model to adopt globalization's penetration to achieve rural-urban integration and rural revitalization for developing countries. This study analyzes the spatial trajectory and dynamics of the Taobao Villages development in Zhejiang Province during 2014-2020. We found that these villages were expanding toward the downtown areas of cities, which led to a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Due to geographical and historical factors, traditional villages in northern Zhejiang region are scattered in distribution, traditional villages in southern Zhejiang region are relatively concentrated, overall, it presents a characteristic of dispersion in the north and concentration in the south (Lin, 2015). The signi cant differences in geographical and historical factors between northern and southern regions of Zhejiang indicate, each traditional village in Zhejiang has distinct regional characteristics and different emphasis.…”
Section: Building Differentiated Brands Based On Regional Characteris...mentioning
confidence: 99%
“…Due to geographical and historical factors, traditional villages in northern Zhejiang region are scattered in distribution, traditional villages in southern Zhejiang region are relatively concentrated, overall, it presents a characteristic of dispersion in the north and concentration in the south (Lin, 2015). The signi cant differences in geographical and historical factors between northern and southern regions of Zhejiang indicate, each traditional village in Zhejiang has distinct regional characteristics and different emphasis.…”
Section: Building Differentiated Brands Based On Regional Characteris...mentioning
confidence: 99%
“…E-commerce reconfigures the socioeconomic environment and physical space of rural areas. Through the Internet and logistics networks, the development of Taobao villages has directly connected a large number of scattered rural areas in China to modern society, freeing them from their isolation from or dependence on urban development for industrial and transportation reasons, thus providing a new path toward rural revitalization (Lin et al, 2022).…”
Section: New Urbanization From Belowmentioning
confidence: 99%
“…Perspectives on the relation between Taobao villages and urbanization are complex. Some studies have discussed the theoretical possibility of Taobao villages contributing to the urbanization level (Lin, 2019;Wang et al, 2021); others have found spillover effects of urbanization in suburban Taobao villages (Lin et al, 2022), and even some Taobao villages far from cities have been urbanized from below (Leong et al, 2016). The influence of Taobao villages on the development of urbanization is worth exploring.…”
Section: Introductionmentioning
confidence: 99%
“…E-commerce, a key aspect of the digital economy, enhances production efficiency [2], improves consumer experiences [3], and fosters innovation and employment [4]. In rural areas, e-commerce offers farmers broader markets and more efficient sales channels [5,6], leading to higher incomes for adopters compared to non-adopters. Studies confirm this significant income increase [7].…”
Section: Introductionmentioning
confidence: 99%